2006
DOI: 10.1159/000095386
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Core Body Temperature of Alzheimer’s Disease Patients as a Possible Indicator of Chronic Neuroinflammation: A Meta-Analysis

Abstract: Background: Neuroinflammation contributes to the pathogenesis of Alzheimer’s disease (AD). Increased pro-inflammatory cytokine levels have been reported in the brain and cerebro-spinal fluid of individuals affected by this neurodegenerative disorder. These same cytokines, including interleukin -1, interleukin-6 and tumor necrosis factor-α, are also believed to be involved in thermoregulation. Furthermore, their effects are thought to be mediated through the induction of cyclooxygenases resulting in increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Construction of nests provides greater warmth and protects animals from environmental conditions (Deacon, 2006; Lynch, 1980). Combined with evidence that people with AD have an increased core-body temperature (likely related to inflammation (Klegeris et al, 2007)), we were led to ask whether the AD-model APP mouse fails to build nests because of thermoregulatory differences. To explore this, we housed 10-12mo old mice for 1 hour over an ice water bath.…”
Section: Resultsmentioning
confidence: 99%
“…Construction of nests provides greater warmth and protects animals from environmental conditions (Deacon, 2006; Lynch, 1980). Combined with evidence that people with AD have an increased core-body temperature (likely related to inflammation (Klegeris et al, 2007)), we were led to ask whether the AD-model APP mouse fails to build nests because of thermoregulatory differences. To explore this, we housed 10-12mo old mice for 1 hour over an ice water bath.…”
Section: Resultsmentioning
confidence: 99%
“…It involves immune cells from the hematopoietic and nervous system 1, 2, 6, 18. It is now well documented that neuroinflammation is actively involved in neurological diseases and disorders, like AD, amyotrophic lateral sclerosis, depression, epilepsy, HD, multiple sclerosis and Parkinson's disease (PD) 19-22. Particularly, in AD, there is a correlation between local inflammation, and presence of amyloid plaques and neurofibrillary tangles 23.…”
Section: Neuroinflammation In Neurological Diseases and Injuriesmentioning
confidence: 99%
“…Molecules released by the immune cells, like interleukins and nitric oxide, regulate negatively adult neurogenesis and may underlie the molecular mechanisms of inflammatory reactions on adult neurogenesis 71, 72. Neuroinflammation is actively involved in neurological diseases and disorders, like AD, depression and PD 19-22. It is proposed that chronic inflammation is a causative factor to the pathogenesis of these neurological diseases and disorders 20, 24.…”
Section: Neuroinflammation In Adult Neurogenesismentioning
confidence: 99%
“…Sustained upregulation of proinflammatory cytokines could also lead to chronically elevated temperature, which could be detrimental to neurons by enhancing neuroinflammatory processes [70]. Even though this has not been demonstrated in PD patients, a meta-analysis of data from six different studies showed a significant increase of core body temperature of Alzheimer's disease patients [71]. This phenomenon could be a direct consequence of local inflammatory reactions in the brain.…”
Section: Cannabinoids and Thermoregulation: A Novel Hypothesis For Thmentioning
confidence: 99%